2012
DOI: 10.1371/journal.pone.0037405
|View full text |Cite
|
Sign up to set email alerts
|

HeT-A_pi1, a piRNA Target Sequence in the Drosophila Telomeric Retrotransposon HeT-A, Is Extremely Conserved across Copies and Species

Abstract: The maintenance of the telomeres in Drosophila species depends on the transposition of the non-LTR retrotransposons HeT-A, TAHRE and TART. HeT-A and TART elements have been found in all studied species of Drosophila suggesting that their function has been maintained for more than 60 million years. Of the three elements, HeT-A is by far the main component of D. melanogaster telomeres and, unexpectedly for an element with an essential role in telomere elongation, the conservation of the nucleotide sequence of He… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“… 121-123 Observations of telomeric retrotransposon regulation in the germline indicate that regulation of these elements is significant to development as sequences targeted by piRNAs in the HeT-A 3′ UTR are highly conserved in D. melanogaster and closely related species. 122 …”
Section: Retrotransposonsmentioning
confidence: 99%
“… 121-123 Observations of telomeric retrotransposon regulation in the germline indicate that regulation of these elements is significant to development as sequences targeted by piRNAs in the HeT-A 3′ UTR are highly conserved in D. melanogaster and closely related species. 122 …”
Section: Retrotransposonsmentioning
confidence: 99%
“…Interestingly, piRNAs are likely to regulate Drosophila telomeric chromatin, which is mostly composed of retrotransposons (reviewed in [72]). In agreement with these observations, specific piRNA targets in the Drosophila telomeric retrotransposon HeT-A have been identified [73]. These targets are conserved in other Drosophila species [73].…”
Section: Pirnasmentioning
confidence: 57%
“…In agreement with these observations, specific piRNA targets in the Drosophila telomeric retrotransposon HeT-A have been identified [73]. These targets are conserved in other Drosophila species [73]. Other instances of piRNA-mediated chromatin regulation involving TEs are still unknown.…”
Section: Pirnasmentioning
confidence: 74%
“…Nevertheless, we have been using the ovary to detect changes in HeT-A and TART expression through quantitative RT-PCR [21], [22]. …”
Section: Resultsmentioning
confidence: 99%
“…The telomere retrotransposons are expressed at low levels and previous studies have shown that HeT-A and TART sense RNAs are not detected by in situ hybridization in the germ line tissues of the Drosophila ovary in wild type conditions [ 19 ], [ 20 ]. Nevertheless, we have been using the ovary to detect changes in HeT-A and TART expression through quantitative RT-PCR [ 21 ], [ 22 ].…”
Section: Resultsmentioning
confidence: 99%